Hybrid 18f-sodium fluoride PET/CT of the thoracic aorta identifies patients at increased risk of stroke. (8th February 2021) - Fletcher, A; Lembo, M; Syed, MBJ; Kwiencinski, J; Tzolos, E; Moss, A; Adamson, PD; Walker, NL; Slomka, PJ; Van Beek, EJR; Newby, DE; Dweck, MR
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship Background: Calcification of the thoracic aorta is associated with poor vessel wall health. Early detection of this disease process may highlight those at risk of future cardiovascular events. Purpose: To investigate the potential of hybrid 18F-sodium fluoride (18F-NaF, a marker of vascular disease and microcalcification activity) positron emission tomography/computed tomography (PET/CT) to predict aortic disease progression and adverse cardiovascular events in patients with established risk factors. Methods: Between 2015 and 2017, 197 patients underwent 18F-NaF PET/CT of the thoracic aorta as part of a randomised controlled trial. Baseline 18F-NaF aortic microcalcification activity (AMA) was calculated as the cumulative uptake in a standardised volume of interest of the arch and ascending aorta. Thirty-seven patients underwent follow up CT enabling aortic calcium score progression calculation. Fatal/non-fatal stroke (primary endpoint) and fatal/non-fatal myocardial infarction (MI, secondary endpoint) were recorded up to May 2020. The association between baseline AMA and both the progression of aortic calcium score and defined endpoints was analysed. AMA was stratified into tertiles (low, moderate or high). Data is presented as mean(SD) or median [IQR]. Results: 18F-NaF AMA correlated with the progression of aortic calcium score (R = 0.42, P = 0.01). During 3.8 (0.9) years of follow up, 14 patients experienced the primary (stroke, n = 5) or secondary (MI, n = 9) endpoint. Patients who experienced stroke had higher AMA (171 [162-176] vs 150 [141 - 157], P = 0.0015). Increased cumulative incidence of stroke was seen in the highest AMA tertile (Figure, P = 0.019). There was no association between AMA and MI (P > 0.05). Conclusion: Aortic microcalcification activity, as measured using 18F-NaF PET/CT, predicts the progression of aortic wall calcification and is associated with an increased risk of stroke but not MI. Consolidating these findings in further studies will improve stroke risk prediction using 18F-NaF PET/CT.